Guideline for assessing risks arising from adoption of a cloud service - Tomčová, Zuzana; Bruckner, Tomáš, 1974-; Vagner, Vlastimil; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2015)
This thesis focuses on assessment of IT risks related to company's adoption of a cloud ser-vice. The goal of the thesis is to identify generally applicable set of IT risks, which will serve as a basis for the proposed risk assessment guideline. The work is organized as follows: Introduction and literature review is presented in the first chapter. The author provides theoretical background supporting better understand-ing of the topic in the Chapter two, where concept of the cloud computing and IT risk are described. A qualitative questionnaire is introduced and results of the participants' re-sponses are depicted in the third chapter. Following chapter provides a risks categoriza-tion representing a base for the proposed cloud oriented IT risk assessment guideline. Subsequently, validation of the guideline in form of its practical application on a company undergoing the decision-making process towards cloud solution is summarized in the Chapter five. Second last chapter describes standards and certifications in an area of coud information security. Finally, Chapter seven summarizes and concludes the findings outlining opportunities for future work and possible improvements in this area.
Vedoucí práce: Tomáš Bruckner
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses